Trust & inspire : how truly great leaders unleash greatness in others - Covey, Stephen M. R., 1962-; Kasperson, David; Covey, McKinlee; Judd, Gary T. (New York : Simon & Schuster, 2022)
"We have a leadership crisis today, where even though our world has changed drastically, our leadership style has not. Most organizations, teams, schools, and families today still operate from a model of "command and control," focusing on hierarchies and compliance from people. But because of the changing nature of the world, the workforce, work itself, and the choices we have for where and how to work and live, this way of leading is drastically outdated. Stephen M.R. Covey has made it his life's work to understand trust in leadership and organizations. In his newest and most transformative book, Trust and Inspire, he offers a simple yet bold solution: to shift from this "command and control" model to a leadership style of "trust and inspire." People don't want to be managed; they want to be led. Trust and Inspire is a new way of leading that starts with the belief that people are creative, collaborative, and full of potential. People with this kind of leader are inspired to become the best version of themselves and to produce their best work. In this "beautifully written page-turner" (Amy Edmondson, Harvard Business School professor), Covey offers the solution to the future of work: where a dispersed workforce will be the norm, necessitating trust and collaboration across time zones, cultures, personalities, generations, and technology. Trust and Inspire calls for a radical shift in the way we lead in the 21st century, and Covey shows us how." --
Introduction -- Part one: The future of leadership: from command & control to trust & inspire. The world has changed, our style of leadership has not -- The increasing irrelevance of command & control -- Style is getting in the way of intent -- Part two: Becoming a trust & inspire leader: the fundamental beliefs and 3 stewardships. The fundamental beliefs of a trust & inspire leader -- The 1st stewardship: modeling, or who you are -- The 2nd stewardship: trusting, or how you lead -- The 3rd stewardship: inspiring or connecting to why -- Stewardship agreements -- What trust & inspire is not -- Part three: Overcoming the 5 common barriers to becoming a trust & inspire leader. Barrier #1: "This won't work here" -- Barrier #2: Fear or "But what if..." -- Barrier #3: "I don't know how to let go" -- Barrier #4: "I'm the smartest one in the room" -- Barrier #5: "This is who I am" -- Part four: The new way to lead in a new world -- Trust & inspire in any context: parenting, teaching, coaching, and more -- Conclusion.
Includes bibliographical references (pages 313-328) and index (329-340).
Keywords: Leadership; Trust; Leadership; Leadership; Confiance; inspiration; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Personal Success; Leadership; Trust; Self-help publications; Informational works; Informational works; Self-help publications